2021
DOI: 10.1083/jcb.202106128
|View full text |Cite
|
Sign up to set email alerts
|

Aurora A kinase activation: Different means to different ends

Abstract: Aurora A is a serine/threonine kinase essential for mitotic entry and spindle assembly. Recent molecular studies have revealed the existence of multiple, distinct mechanisms of Aurora A activation, each occurring at specific subcellular locations, optimized for cellular context, and primed by signaling events including phosphorylation and oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 17 publications
0
25
1
Order By: Relevance
“…While the latter kinases are known mediators in FAK signaling pathways, such a connection has not been reported for Aurora A. The regulation of Aurora A is complex and several different activation mechanisms have been elucidated [46], including binding to Ser112phosphorylated Bora, autophosphorylation at Thr288 after interactions with Tpx2, and transphosphorylation after interactions with Cep192 [47]; furthermore, PAK1 was shown to promote Aurora A Thr288 phosphorylation [48]. Thus, further investigations are needed to clarify how FAK regulates PLK1 activity, possibly via Aurora A.…”
Section: Discussionmentioning
confidence: 99%
“…While the latter kinases are known mediators in FAK signaling pathways, such a connection has not been reported for Aurora A. The regulation of Aurora A is complex and several different activation mechanisms have been elucidated [46], including binding to Ser112phosphorylated Bora, autophosphorylation at Thr288 after interactions with Tpx2, and transphosphorylation after interactions with Cep192 [47]; furthermore, PAK1 was shown to promote Aurora A Thr288 phosphorylation [48]. Thus, further investigations are needed to clarify how FAK regulates PLK1 activity, possibly via Aurora A.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms involved in the spatio-temporal regulation of Aurora-A rely on the binding of co-factors that allosterically regulate Aurora-A, either inducing (CEP192, TPX2 and Ajuba), or not (Bora), its auto-phosphorylation on threonine 288 (Thr288), a residue positioned within the activation loop that is generally associated with the enhancement of its kinase activity [ 77 , 78 , 79 , 80 , 81 ]. Nevertheless, in some cases the phosphorylation on Thr288 is necessary but not sufficient to fully activate Aurora-A [ 82 ]. Indeed, phosphorylation, acetylation and SUMOylation on alternative residues by other enzymes are important to regulate Aurora-A activity and functions [ 61 , 83 , 84 , 85 , 86 , 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…PLK1 activity is known to be controlled by phosphorylation at Thr210 in the activation loop by Aurora A ( Gheghiani L et al, 2017 ; Raab M et al, 2022 ), and additional PLK1 modifications have been reported, which may further contribute to its spatiotemporal regulation ( Caron D et al, 2016 ; Liu X et al, 2016 ; Yang X et al, 2017 ). Also, the regulation of Aurora A is complex, and several different activation mechanisms have been elucidated ( Zhao Z S et al, 2005 ; Tavernier N et al, 2021 ). Thus, while the mechanism by which FAK promotes PLK1 activity remains to be identified, it is likely to act in parallel with or possibly upstream of Aurora A.…”
Section: Spindle Formationmentioning
confidence: 99%